2009
DOI: 10.1007/s10459-009-9207-x
|View full text |Cite
|
Sign up to set email alerts
|

The testing effect on skills learning might last 6 months

Abstract: In a recent study we found that testing as a final activity in a skills course increases the learning outcome compared to spending an equal amount of time practicing. Whether this testing effect measured as skills performance can be demonstrated on long-term basis is not known. The research question was: does testing as a final activity in a cardio-pulmonary resuscitation (CPR) skills course increase learning outcome when assessed after half a year, compared to spending an equal amount of time practicing? The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 12 publications
3
66
3
Order By: Relevance
“…161 End-of-course assessment may be useful in helping learners retain skills (Class IIb, LOE C). • Simplification -Course content should be simplified in both the presentation of the content and the breadth of content in a single course in order to facilitate accomplishment of course objectives.…”
Section: Post-course Assessmentmentioning
confidence: 99%
“…161 End-of-course assessment may be useful in helping learners retain skills (Class IIb, LOE C). • Simplification -Course content should be simplified in both the presentation of the content and the breadth of content in a single course in order to facilitate accomplishment of course objectives.…”
Section: Post-course Assessmentmentioning
confidence: 99%
“…The rise of simulation-based education focusing on the acquisition of specific skills relevant to medical practice has renewed the interest in both knowledge retention and specific strategies aiming at the maintenance of what is learned. A number of studies have shown that concentrated learning and training, as well as repeated testing are able to improve performance related to specific skills, such as those involved in advanced cardiac life support [8,9], advanced trauma life support [10], general surgery [11] and laparoscopic skills [12], drug administration skills [13], cardiopulmonary resuscitation skills [14], central venous catheter insertion skills [15], critical obstetrical events [16] and general knowledge on life support [17], amongst others.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results in other studies have provided evidence of the long-term effects of testing. 13 In the authors' second course, they found that those who had received the course scored worse than those who had no exposure to the information; this difference was also not statistically significant. This divergence in results is consistent with a topic effect in the second course, where the materials and learning strategy may not have been the right fit to produce a gain in knowledge.…”
mentioning
confidence: 92%